True stress-control ratcheting behaviour of cold-rolled interstitial-free steel sheet. (December 2017) - De, ParthaSarathi; Mahato, Jayanta Kumar; Kundu, Amrita; Chakraborti, P.C.; Shome, M.
Highlights: Mean stress induced hardening improves ratcheting-fatigue life at fixed σ a . Higher back stress amplitude at fixed σ m results in higher ratcheting strain. Increase of R at fixed σ max results in lowering of ratcheting deformation. Predominantly intergranular failure occurs at low stress amplitude. Abstract: True stress-control ratcheting behaviour of 2.3 mm thick titanium stabilised interstitial-free steel has been investigated under constant maximum stress, constant mean stress and constant stress amplitude conditions until complete failure of the specimens. The ratcheting strain to failure, and cycles to failure under different stress conditions have been rationalised by considering the evolution of back stresses vis-a-vis total and net cyclic plastic strain response. It is found that higher stress asymmetry due to increase of stress ratio at constant maximum stress results in lower ratcheting deformation. This happens due to both mean stress assisted hardening and lower back stress amplitude resulting from decreasing stress amplitude. On the other hand, mean stress induced hardening improves ratcheting-fatigue life at constant stress amplitude. The amplification of cyclic plastic strain response with increase of stress amplitude at constant mean stress results in higher ratcheting strain accumulation at higher stress amplitude.